Is Ferroptosis a Future Direction in Exploring Cryptococcal Meningitis? - Xu, Xianbin; Lin, Danfeng; Tu, Sheng; Gao, Shiqi; Shao, Anwen; Sheng, Jifang (Frontiers in Immunology, 2021)
Cryptococcal meningitis (CM) is the leading cause of mortality among patients that are infected with human immunodeficiency virus (HIV). Despite the fact that the current treatment strategies for CM are continually being developed, the mortality rate is still high. Therefore, we need to explore more therapeutic strategies that are aimed at hindering its pathogenic mechanism. In the field of CM, several studies have observed rapid iron accumulation and lipid peroxidation within the brain, all of which are hallmarks of ferroptosis, which is a type of programmed cell death that is characterized by iron dependence and lipid peroxidation. In the recent years, many studies have confirmed the involvement of ferroptosis in many diseases, including infectious diseases such as Mycobacterium tuberculosis infection and coronavirus disease-2019 (COVID-19). Furthermore, ferroptosis is considered as immunogenic and pro-inflammatory as the ferroptotic cells release damage-associated molecular pattern molecules (DAMPs) and alarmin, both of which regulate immunity and pro-inflammatory activity. Hence, we hypothesize that there might be a relationship between this unique cell death modality and CM. Herein, we review the evidence of ferroptosis in CM and consider the hypothesis that ferroptotic cell death may be involved in the cell death of CM.